KINERJA TANGGUNGJAWAB SOSIAL PERUSAHAAN (CSR) KAWASAN INDUSTRI DI KABUPATEN SERANG TERLEMAH DI PROVINSI BANTEN - Djasuro Djasuro (Sains: Jurnal Manajemen dan Bisnis, 2018)
Mandate of the law no. 40 of 2007 on limited liability companies, Article 74 paragraph 1 of the Company said that their business activities in the field and / or related to the natural resources required to implement the Social and Environmental Responsibility. This means an obligation for the company concerned. Failing to implement CSR programs, the company has violated the rules of law contained in the legislation. CSR program if implemented properly by a company turned out to be a positive impact on the image and reputation of the company. that a company in carrying out CSR programs should pay attention to aspects that not only the material needs of communities in a corporate environment, but also that the implementation of CSR programs is done in a way that can provide comfort and Preserve the natural environment and corporate communities integrally. Studies done is to determine the extent of implementation of CSR programs in the existing industrial area diprovinsi Banten, and industrial areas which showed the weakest value. Assessment methodology used is quantitative descriptive analysis was based on a questionnaire distributed to the public the existing industrial area diprovinsi Banten who number as many as 702 respondents. Based on the results of data processing is concluded that the implementation of CSR by companies in the industrial area of Banten province according to public perception of environment companies uncategorized medium (performance 67.24), and the implementation of the CSR of the lowest in the industrial area in the district of Serang ( performance 60.5) while the other industrial areas have the performance from 68.97 to 76.30 is entered in both categories.